Predicting signatures of anisotropic resonance energy transfer in dye-functionalized nanoparticles. Issue 106 (2nd November 2016) - Gil, Gabriel; Corni, Stefano; Delgado, Alain; Bertoni, Andrea; Goldoni, Guido
Abstract : Strategy to expose anisotropic signatures of resonance energy transfer (RET) in the photoluminescence (PL) from a single dye-functionalized nanoparticle (NP) irradiated with light linearly polarized along the bright plane or the dark axis of the NP. Abstract : Resonance energy transfer (RET) is an inherently anisotropic process. Even the simplest, well-known Förster theory, based on the transition dipole–dipole coupling, implicitly incorporates the anisotropic character of RET. In this theoretical work, we study possible signatures of the fundamental anisotropic character of RET in hybrid nanomaterials composed of a semiconductor nanoparticle (NP) decorated with molecular dyes. In particular, by means of a realistic kinetic model, we show that the analysis of the dye photoluminescence difference for orthogonal input polarizations reveals the anisotropic character of the dye–NP RET which arises from the intrinsic anisotropy of the NP lattice. In a prototypical core/shell wurtzite CdSe/ZnS NP functionalized with cyanine dyes (Cy3B), this difference is predicted to be as large as 75% and it is strongly dependent in amplitude and sign on the dye–NP distance. We account for all the possible RET processes within the system, together with competing decay pathways in the separate segments. In addition, we show that the anisotropic signature of RET is persistent up to a large number of dyes per NP.